Improving the larvae acceptance rate and morphometric characteristics of queen Apis cerana javana by grafting larvae at different ages (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ustadi, Ikhsan N, Junus M, Suyadi. 2021. Improving the larvae acceptance rate and morphometric characteristics of queen Apis cerana javana by grafting larvae at different ages. Biodiversitas 23: 166-170. This study was aimed to evaluate the effect of different ages of grafted larvae on the acceptance rate and morphometric characteristics of queen Apis cerana javana Fabr. The total of 72 larvae were 1, 2, and 3 days old and was reared in 7 colonies with 3 treatments (larvae age) and 6 replications. The morphometrics studied consisted of body length, emergence weight, head length, head width, thorax length, thorax width, fore wing length, fore wing width, abdomen length, and abdomen width. The results showed that the different ages of grafted larvae had a highly significant on body length, emergence weight (P
Keywords: Grafted age, larvae, morphometrics, queen rearing